Maturation, pharmacogenomics and metabolomics as factors determining pharmacokinetic and pharmacodynamics profile of alpha-agonist in pediatric intensive care unit patients - Bartkowiak-Wieczorek, Joanna; Mocarska, Justyna; Bartkowska-Śniatkowska, Alicja; Matysiak, Jan; Klupczyńska, Agnieszka; Kokot, Zenon J.; Wiczling, Paweł; Grześkowiak, Edmund; Bienert, Agnieszka (Journal of Medical Science, 2016)
Research Project Objectives. Project entitled “Maturation, pharmacogenomics, and metabolomics as factors determining pharmacokinetic and pharmacodynamic profile of alpha-agonist in pediatric intensive care unit patients” was founded by the Polish National Science Center (NCN) under project number: 2015/17/B/NZ7/03032. The duration of the grant is 36 months, and the total grant value is 688800 PLN. The project is run by the Medical University of Gdansk and Poznan University of Medical Sciences. The aim of this grant is to examine the influence of maturation, pharmacogenetics, metabolomics and physiological (or pathophysiological) status of the patients on the pharmacokinetics and pharmacodynamics (PK/PD) of ?2-adrenergic drugs (dexmedetomidine and clonidine) in pediatric population. The project was proposed to explain the unusual PK of dexmedetomidine reported in literature and in our preliminary experiments, in which a two-fold increase in dexmedetomidine clearance was observed during prolonged (lasting more than 24 hr) infusions in the intensive care unit patients. General information. Project entitled “Maturation, pharmacogenomics, and metabolomics as factors determining pharmacokinetic and pharmacodynamics profile of alpha-agonist in pediatric intensive care unit patients” was founded by the Polish National Science Center (NCN) under project number: 2015/17/B/NZ7/03032. The duration of the grant is 36 months, from 2016-04-27 to 2019-04-26 and the total grant value is 688800 PLN. The project is run by the Medical University of Gdansk and Poznan University of Medical Sciences. The research group consists of: principal investigator dr hab. Paweł Wiczling and co-investigators: dr hab. Agnieszka Bienert, dr Alicja Bartkowska-Śniatkowska, dr Joanna Bartkowiak-Wieczorek, mgr Justyna Mocarska, prof. Edmund Grześkowiak, dr Jan Matysiak, mgr Agnieszka Klupczyńska, dr Danuta Siluk, mgr Agnieszka Borsuk and prof. dr hab. Zenon J. Kokot. The Ethical Committee permission number is 261/15.